Design and development of atypical multicopters with application to heptacopter - Leung, Sheila Sook Hui (2015)
Many industries have been exploring the idea of using unmanned aerial vehicles, commonly known as drones, for some of their operations since the 1990s. Especially in recent years, many individuals have been developing control systems and hardware components for multi-rotor copters. Quadcopters are multi-rotor copters with four rotors and these are most commonly seen in the market currently. Based on the working principles of quadcopters, including the construction of the hardware and design of software, these concepts will be applied to atypical multi-rotor copters with odd number of rotors. This report documents the hardware selection and construction process of various types of multi-rotor copters. Furthermore, description of the electronic and mechanical components will be given and summarized in a schematic diagram showing how each part is connected to other components. In addition, the software that supports the stabilization and configuration of the Pixhawk control system will be introduced. The firmware for atypical multi-rotor copters is not comprehensively developed due to limited applications in the present. Therefore, the design and development of atypical multi-rotor copters will be extensively discussed. This includes the tuning of controls and the modification of some parts of the firmware to suit the needs of atypical multi-rotor copters. Some possible applications of atypical multi-rotor copters will be pointed out as well. Lastly, discussion will be conducted, starting with the significance of introducing atypical multi-rotor copters into the market. Following that, some of the challenges faced during the project will be brought up and solutions used to resolve these problems will be discussed as well. Subsequently, several areas of future research with regards to atypical multi-rotor copters will be suggested.The report ends off with attachment of technical data of the components installed on the multi-rotor copters used for this project.